Effect of Macroeconomic Factors on Firms ROA: A Comparative Sectorial Analysis from Pakistan - Mohd, Ali Shah; Siddiqui, Danish Ahmed (International Journal of Publication and Social Studies, 2020)
The effect of firm level factors or industry specific determinants on company performance has been worked on in Pakistan but the researches are mainly focused on textile industries and to an extent agro food industry. This study has been conducted on the effect of macroeconomic factors on firm performance in Pakistan with the focus being on seven industries. 10-year data of 5 companies each in 7 industries in Pakistan (35 companies) was collected through the financial reports, from their official websites. Seven industries were selected the Sugar, Textile, Garments, Automotive, Food, Ceramics and Cement industries. The effect of macro-economic factors like Inflation Rate, Real Effective Exchange Rate, Foreign direct investment and Unemployment Rate, as well as Unit Labor Cost, were assessed on Return on Assets for each industry using separate regressions. The results indicated that inflation was a significant factor in sugar industry whereas labor unit cost and exchange rate significantly contributed to textile industry firm performance. Garment and auto industry firm performance were heavily influenced by inflation and unemployment. Lastly food and cement industry ROA were greatly influence by rate of exchange and FDI. Whereas these macroeconomic factors had very little impact on Ceramic industry. These results can assist managers, company auditors, lenders, and regulatory bodies to identify businesses that will be affected by macroeconomic changes and use this information to improve future performance.